2017
DOI: 10.3389/fnins.2017.00364
|View full text |Cite
|
Sign up to set email alerts
|

Leftward Deviation and Asymmetric Speed of Egocentric Judgment between Left and Right Visual Fields

Abstract: The egocentric reference frame is essential for body orientation and spatial localization of external objects. Recent neuroimaging and lesion studies have revealed that the right hemisphere of humans may play a more dominant role in processing egocentric information than the left hemisphere. However, previous studies of egocentric discrimination mainly focused on assessing the accuracy of egocentric judgment, leaving its timing unexplored. In addition, most previous studies never monitored the subjects' eye po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Our study found a slight rightward bias in midline landmark perception (and indeed for the majority of body landmarks in the horizontal direction), in line with Kolb et al (2012) where participants eyes were also closed, and so this rightward shift may also be due to participants performing the task with no visual input. This rightward bias is opposed to the majority of the above studies, where participants could use their vision, and thus further engage the right hemisphere, potentially causing a leftward shift in midline as suggested above, with the relationship between the right hemisphere and vision, when visual input is used (Reinersmann et al, 2012;Zhou et al, 2017). A further fundamental methodological difference in the current study that may explain differences with results from previous studies, centres on participants relying on an internal reference system of their body to identify body landmarks and estimate midline on their own body, as opposed to predicting midline via an illuminated dot or pointing straight ahead, which may be argued to link midline predictions to an external point to the body.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our study found a slight rightward bias in midline landmark perception (and indeed for the majority of body landmarks in the horizontal direction), in line with Kolb et al (2012) where participants eyes were also closed, and so this rightward shift may also be due to participants performing the task with no visual input. This rightward bias is opposed to the majority of the above studies, where participants could use their vision, and thus further engage the right hemisphere, potentially causing a leftward shift in midline as suggested above, with the relationship between the right hemisphere and vision, when visual input is used (Reinersmann et al, 2012;Zhou et al, 2017). A further fundamental methodological difference in the current study that may explain differences with results from previous studies, centres on participants relying on an internal reference system of their body to identify body landmarks and estimate midline on their own body, as opposed to predicting midline via an illuminated dot or pointing straight ahead, which may be argued to link midline predictions to an external point to the body.…”
Section: Discussionmentioning
confidence: 91%
“…The rightward shift in the current study contrasts with a previous review of literature reporting a leftward shift in mid-sagittal pointing tasks ( Jewell & McCourt, 2000 ). A leftward shift in midline perception has been argued due to the right-hemisphere dominance in visuospatial ( Reinersmann et al, 2012 ) and egocentric processing ( Zhou et al, 2017 ), and the potential greater representation of the ipsilateral visual field in the right hemisphere compared to the left ( Zhou et al, 2017 ). Our study found a slight rightward bias in midline landmark perception (and indeed for the majority of body landmarks in the horizontal direction), in line with Kolb et al (2012) where participants eyes were also closed, and so this rightward shift may also be due to participants performing the task with no visual input.…”
Section: Discussionmentioning
confidence: 99%